(untitled) (Journal of actual problems of jurisprudence, 2022)
This article is devoted to determining the state’s role in preventing new challenges and threats in the modern period. New challenges and threats are identified by analyzing problematic issues related to ensuring national security is carried out. Particular attention is paid to the problems of ensuring the coordinated functioning and interaction of state bodies. The authors believe that violation of the principle of ensuring the unity of state power can lead to negative consequences for the entire system of the state. It is proposed to analyze all regulatory legal acts of a subordinate nature to identify the reasons that hinder the coordinated interaction of state bodies. One of the primary tasks in ensuring national security is ensuring external security and countering terrorism. It is concluded that special attention of all state bodies should be paid to strengthening state independence, the integrity of the state, and the unity of the people based on a single territory, single citizenship, a single supreme authority, a single system of law, a single state language. Keywords: ensuring national security, coordinated functioning and interaction, unity of state power, countering terrorism.